Economic conditions and incumbent support in Africa's new democracies: evidence from Zambia - Posner, Daniel N.; Simon, David J. (2002)
In this article, the authors investigate the effects of economic conditions on support for an incumbent regime in a new African democracy. Drawing on two unique data sources from Zambia - the results of a 1,200 - respondent post election survey and a pair of 10,000-household poverty surveys conducted in the same years as that country's first two posttransition general elections - the authors find evidence that declining economic conditions coincide with the withdrawal of support for the incumbent president, although the effects of changing economic conditions are relatively small compared to noneeconomic determinants of the vote such as ethnic affiliation and urban/rural location. The authors also find that, to the extent that voters respond to declining economic conditions, they do so via withdrawal from the electoral process rather than via support for the opposition. The findings suggest that African electorates are at least modestly responsive to economic trends but that noneeconomic motivations still predominate in any given election. - Reproduced.
Keywords: Economic conditions